What’s so special about Ethiopian politics? - Ramos, M. (9º Congresso Ibérico de Estudos Africanos, 2014)
This paper proposes to tap both into the history of Ethiopian-Western relations and the multifactorial proclivities of that country’s political system to understand: 1) How international expectations about the democratization and accountability of the Ethiopian ethnic federal system are fed by elaborate and tightly-controlled translation and PR practices, while at the same time maintaining traditional procedures of power politics, and; 2) What this split may say about the limitations of a (mostly Western-grounded) transnational-transcultural-translinguistic framework for typifying political systems. Furthermore, it proposes to discuss the rise of Muslim-based political agency in Ethiopia within the wider framework of the Horn of Africa - particularly considering the factitious nature of the region’s state-making processes